Effects of bioformulation prototype and bioactive extracts from Agaricus bisporus spent mushroom substrate on controlling Rhizoctonia solani of Lactuca sativa L - Cignola, Rudy; Carminati, Gaia; Natolino, Andrea; Di Francesco, Alessandra (Frontiers in Plant Science, 2024)
Food security and waste management represent among the main challenges those to be addressed in the near future. The use of bioformulations and bioactive compounds obtained from agricultural wastes could represent some of the solutions for the management of soil-born pathogens. In the present study, Aureobasidium pullulans strain AP1, tested in oil dispersion (OD) formulation prototype and bio-extracts (HWE, hot water extract and WWE, warm water extract) derived from spent mushroom substrate (SMS) of Agaricus bisporus, were tested as sustainable strategies to manage Rhizoctonia solani of lettuce. By in vitro assays, AP1OD at 600 mg L -1 displayed an inhibition by 57% of pathogen mycelial growth and the SMS extract WWE (40 °C) showed a growth stimulation of lettuce seedling by 27%. In vivo assays, AP1OD formulation used against R. solani reduced by 66.6% the soil-borne pathogen incidence on lettuce plants and both bio-extracts significantly stimulated lettuce leaves and roots growth (>200%). AP1OD formulation and HWE treatments increased the lettuce genes expression levels (ggps, hppd pdx1) mainly imputed to plant antioxidant potential, vitamin E and vitamin B6 biosynthesis. The present study reported the potential of a new formulation and two bio-extracts, derived from an agricultural waste, to use against R. solani of lettuce respectively with antifungal and biostimulant properties.